A genome-centric metagenomics approach to explain microbial community structure in anaerobic digesters - Neshat, Soheil Asgarineshat (2022)
A functioning anaerobic digestion (AD) microbiome is integral for sludge management to be successful. Comprehensive ecological insights, and a full accounting of important microbial species, can help to improve and validate operational strategies. We analysed a time-series of metagenome samples obtained from full-scale anaerobic digesters and performed genome-resolved analysis to gain insight into the microbial community structure and potential functions of the AD microbiome. Ninety samples from three full-scale digesters were collected over a period of nine months and their nucleic acids extracted and subjected to shotgun sequencing (Illumina HiSeq2500; average 70M PE reads/sample). The raw reads were quality controlled, trimmed, assembled, binned, and dereplicated to obtain metagenome-assembled genomes (MAGs). Genome quality was assessed using the MIMAG criteria. The taxonomic assignment of the recovered MAGs was conducted using GTDB-Tk, and gene-level functional annotations were obtained using the KEGG, and CAZy databases. From ninety metagenome assemblies, 14,236 MAGs were recovered, of which 37%, 16%, and 1% satisfied medium-quality (Completeness > 50% and contamination <10%), putative high-quality (Completeness > 90% and contamination <5%), and high-quality criteria (Completeness > 90% and contamination <5% and presence of rRNA and tRNA genes), respectively. Taxonomical classification of the MAGs with at least medium quality (n =7666) revealed that 12.9%, 37.4%, and 77.1% of them belong to a novel family, genus, and species, respectively. A co-occurrence network analysis of the community structures in three replicate digesters revealed a highly interconnected network of microorganisms, suggesting the presence of a backbone in a functional AD microbial community. Functional analysis of the recovered MAGs showed the presence of three methanogenesis pathway modules, namely, methanogenesis via CO2, acetate, and trimethylamine. In addition, a specialization was observed in the hydrolytic bacterial community using CAZy annotation. In conclusion, we have obtained a catalogue of 166 MIMAG high-quality MAGs from a time-series metagenome survey of three full-scale anaerobic digesters situated in a tropical wastewater treatment plant, leading to novel ecological insights into the AD microbial community.